TRADISI ULAMA TRANSFORMATIF MINANGKABAU DALAM MEMBANGUN PENDIDIKAN KARAKTERISTIK BERBASIS RESPONSIF TEOLOGIS DAN KONTRIBUSINYA TERHADAP PENGUATAN MORALITAS - Silfia Hanani (Lembaga penelitian dan pengabdian kepada Masyarakat, 2015)
Minangkabau is one of the ethnic groups in Indonesia where local social context strongly influenced by social designs built by scholars as one of the local elite, as scholars here plays a big build community through the code of conduct characteristic of a responsive approach to theological education. Theological responsive characteristics was described by scholars transformative, the scholars who controlled sociological lokas that the presence of religion that feels as responsive theological moral values and religious teachings can be internalized in the social life of the community. Theological responsive it is basically inherent in the educational characteristics established by scholars in educational institutions surau as initial educational institutions for the Minangkabau. Responsive theological scholars characteristics of transformative education, the scholars not just spreading the ideas to change society and the individual, but also a prominent cleric transformative reference, so that the cleric was an icon morality. In the present condition of national morality, the role of the ulama transformative theological education responsive characteristics, be an alternative to improve the morality of a nation torn apart again, this time because of the moral crisis caused by the loss of educational institutions to internalize the moral values builder it. Cleric transformative Minangkabau with agencies and educational institutions through the development surau responsive characteristics of theological education has obvious positive implications for the development of a civilized moral nation.